MIRAGRODEP Dual-Dual (MIRAGRODEP -DD) with an application to the EU-Southern African Development Community (SADC) Economic Partnership Agreement (EPA) - Bouët, Antoine; Laborde Debucquet, David; Traoré, Fousseini (International Food Policy Research Institute, 2021)
MIRAGRODEP Dual-Dual is a recursive-dynamic multi-region, multi-sector computable general equilibrium model, devoted to trade and agricultural analysis. It is developed for AGRODEP and draws upon the MIRAGE model built by CEPII. It incorporates specific features of African economies. In addition to the usual dichotomy between rural and urban activities, it also features the distinction between formal and informal activities (double dualism a la Stifel-Thorbecke). The model includes other features such as foreign direct investment and runs with a tariff aggregation module that allows the user to capture the exclusion effects at a detailed level and the variance of tariffs. The model also includes a submodule allowing to test different closures for the public sector as well as the inefficiency of the tax collection system. Social Accounting Matrix (SAM) and trade data in MIRAGRODEP are based on the GTAP database. Additional sources such as MacMap are used for protection data.